Understanding the lived experiences of healthcare professionals during the COVID-19 pandemic: an interpretative phenomenological analysis - Emily McGlinchey; Catherine Hitch; Sarah Butter; Laura McCaughey; Emma Berry; Cherie Armour (European Journal of Psychotraumatology, 2021)
Background: Little research has examined the impact of working within the context of COVID-19 on UK healthcare professionals (HCPs) mental health and well-being, despite previous pandemic findings indicating that HCPs are particularly vulnerable to suffering PTSD and other mental health difficulties due to the nature of healthcare work. Specifically, it appears that no research has employed qualitative methodologies to explore the effects of working amidst COVID-19 on mental health for HCPs in the UK. Objective: To qualitatively examining the lived experiences of HCPs in Northern Ireland, working during the early stages of the pandemic and lockdown period (14.04.20 and 29.04.20). Method: Interpretative phenomenological analysis (IPA) was used to explore the experiences of healthcare professionals, who were working during the COVID-19 outbreak. Ten HCPs were recruited via a social media campaign and snowball sampling. All interviews were conducted via telephone and transcribed verbatim. Results: Three superordinate themes with subordinate themes were elicited through the analysis. Theme one centred on specific challenges of HCPs working during the pandemic, such as redeployment, isolation from loved ones, infection concerns, lack of PPE and impact on patient interpersonal care. Theme two offered insights into the mental health and wellbeing of HCPs, while many experienced feelings of fear, sadness and hypervigilance, all also demonstrated a marked resilience. Finally, many felt undervalued and misunderstood, and wished to press upon the general public seriousness of the disease. Conclusion: To the authors’ knowledge this is the first study to explore in depth, the unique experiences of frontline HCPs in Northern Ireland, offering a detailed account of the challenges confronted in these unprecedented circumstances and highlighting support needs within this cohort.